Ion Pairing in Aqueous Metal Sulfates and Platinum Group Metal Ammonium Solutions - Matthews, Richard P (Department of Chemistry, 2014)
The structure and dynamics of ions and ion pairs in solution play an integral part in several biological and chemical processes. Historically the calculation of ion pair association constants from computer simulations has been complicated due to the difficulty in validating metal ion force fields for solution simulations. In this thesis a force field for divalent metal ions in metal sulfate solutions (i.e. Mg2+SO4 2-, Ca2+SO4 2-, Mn2+SO4 2-, Fe2+SO4 2-, Co2+SO4 2-, Ni2+SO4 2-, Cu2+SO4 2- and Zn2+SO4 2-) important in physical and biophysical experiments is produced. Potential of mean force calculations are used to provide ion pair free energy profiles and free energy perturbation calculations are used to calibrate the potential of mean force (PMF) from which association constants for ion pairs can be produced for these metal sulfate solutions. The calibrated free energy profiles result in calculated association constants that are in excellent agreement with available experimental data where available. Consequently the force field has been shown to be accurate for simulations of biophysical and physical systems. Furthermore the method, proposed in this thesis, for calibrating PMFs and calculating detailed association constants from those curves can most likely be used for complex systems that have previously been computationally inaccessible. Next a detailed account of solvation structures and the nature of ion pair formation mechanisms for important metal sulfates in aqueous media are presented. Radial and spatial distribution functions calculated for several ion pair species reveal that the transition from free ions to contact ion pairs involves the loss of between one to two water molecules from the cation depending on the cation size. This is correlated with the experimental hydration numbers calculated for metal sulfate electrolyte solutions at several concentrations using density and ultrasonic velocity measurements. These experiments reveal a decrease in hydration number with an increase in concentration, which can be attributed to the formation of ion pairs. A more complex metal system is the industrially important platinum group metal (PGM) chloro-anion one. Their industrial importance relates to the search for a Green Chemistry Process for the separation of PGM chloro complexes that have been extracted from the mined ore into an acidic aqueous media. This requires a PGM separation process in water. Here an understanding of the hydration structure about the iii PGM chloro-anion complexes and the role that ammonium counter-ions play in disrupting that solvent structure when ammonium PGM salts are formed, is critical in the process design. To this end a solution force field, inclusive of the majority of PGM chloro-anion complexes (i.e. (Y)2[PtCl4]2-, (Y)2[PdCl4]2-, (Y)2[PtCl6]2-, (Y)2[PdCl6]2-, (Y)2[IrCl6]2-, (Y)2[OsCl6]2-, (Y)2[RuCl6]2-, (Y)3[IrCl6]3-, (Y)3[RhCl6]3- and (Y)3[RuCl6]3- , where Y = NH4 +) arising in acidic aqueous media, parameterised from experimental and quantum mechanically derived properties, was developed. Nanosecond atomistic molecular dynamics simulations were then performed for the PGM chloro-anion complexes. Analysis of the solvation structure using radial and spatial distribution functions revealed two distinct solvent structures corresponding to the square planar and octahedral species. The formation of ion pairs disrupts the solvent structure where the hydration shells about the bivalent hexachlorometallates are more affected compared with the trivalent hexachlorometallates and these first shell waters in turn are more affected than those in the bivalent tetrachlorometallates. Finally to inform the design of a separation process transport properties such as diffusion coefficients, ion hydration numbers and water residence times for the PGM chloro-anion complexes were calculated. It is observed that the diffusion rates of PGM chloro-anion complexes are strongly correlated to their ion hydration numbers as calculated by Voronoi tessellation of the simulation cell, such that a larger hydration shell volume results in a slower PGM chloro-anion diffusion rate.